PENGARUH SISA HASIL USAHA (SHU) PADA KOPERASI MENGGUNAKAN REGRESI LINEAR BERGANDA - Ikram Mawar Sari; Achi Rinaldi; Fredi Ganda Putra (MAJU : Jurnal Ilmiah Pendidikan Matematika, 2020)
Abstrak:  This study aims to find out what factors can affect the Remaining Operations in Bunga Tanjung Credit Cooperative and find out which factors are the most influential. This research is a quantitative study using multiple linear regression analysis methods. The data used in this research is secondary data. The independent variable in this study is the number of members, the number of deposits and the amount of capital, while the dependent variable in this study is the Remaining Results. Based on the test results obtained the number of members, the number of deposits, and the amount of capital have a significant effect simultaneously on the Remaining Results of the Bunga Tanjung Cooperative Credit Business in North Lampung Regency. Partially, the variable results of the number of members, the number of deposits and working capital have a positive and significant effect on the remaining results of the Bunga Tanjung Cooperative Credit Business Results in North Lampung Regency. While the value of R ^ 2 shows the number 0.924 which means that 92.4% of the change in residual results of operations is caused by the number of members, the number of deposits and the amount of capital. While the remaining 7.6% changes in the remaining results of operations are caused by other variables not included in this study. Keywords:  linear regression analysis, cooperative, remaining business result.